2020
DOI: 10.1111/tpj.14907
|View full text |Cite
|
Sign up to set email alerts
|

The key role of terminators on the expression and post‐transcriptional gene silencing of transgenes

Abstract: Transgenes have become essential to modern biology, being an important tool in functional genomic studies and also in the development of biotechnological products. One of the major challenges in the generation of transgenic lines concerns the expression of transgenes, which, compared to endogenes, are particularly susceptible to silencing mediated by small RNAs (sRNAs). Several reasons have been put forward to explain why transgenes often trigger the production of sRNAs, such as the high level of expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 66 publications
(111 reference statements)
5
66
0
Order By: Relevance
“…For instance, transient expression efficiency of GFP using viral replicons is dramatically improved when multiple introns are added to the reporter sequence ( Marillonnet et al, 2005 ). A similar effect was also observed when an intron-containing GFP transgene was agro-infiltrated in Nicotiana benthamiana leaves, although this effect was dependent on the accompanying terminator sequence ( de Felippes et al, 2020 ). Furthermore, the abundance of RDR6-dependent siRNAs originating from a 35S-driven transgene is reduced when a GFP containing introns is used ( Christie et al, 2011 ).…”
Section: Factors Triggering Transitivitymentioning
confidence: 62%
See 4 more Smart Citations
“…For instance, transient expression efficiency of GFP using viral replicons is dramatically improved when multiple introns are added to the reporter sequence ( Marillonnet et al, 2005 ). A similar effect was also observed when an intron-containing GFP transgene was agro-infiltrated in Nicotiana benthamiana leaves, although this effect was dependent on the accompanying terminator sequence ( de Felippes et al, 2020 ). Furthermore, the abundance of RDR6-dependent siRNAs originating from a 35S-driven transgene is reduced when a GFP containing introns is used ( Christie et al, 2011 ).…”
Section: Factors Triggering Transitivitymentioning
confidence: 62%
“…During transcription, sequences in the terminator region are recognized by the 3′ end processing machinery resulting in the addition of a poly(A) tail to the nascent transcript and triggering the end of the polymerization process by the RNA polymerase II ( Mandel et al, 2007 ; Kumar et al, 2019 ; Thore and Fribourg, 2019 ). A growing number of studies have shown that different terminators can have a distinct influence in the efficiency of transgene expression ( Ingelbrecht et al, 1989 ; Nagaya et al, 2009 ; Yang et al, 2009 ; Hirai et al, 2011 ; Pérez-González and Caro, 2018 ; de Felippes et al, 2020 ). The improper formation of the mRNA 3′ end has also been implicated with enhanced silencing of transgenes.…”
Section: Factors Triggering Transitivitymentioning
confidence: 99%
See 3 more Smart Citations